Legal Certainty in Housing Development on Protected Rice Paddy Land: A Case Study of the Pendawa Housing Estate, Lebaksiu, Tegal Regency - Muhamad Noval Arahman; Abdul Basit; Iin Ratna Sumirat (LPPM Universitas Harapan Bangsa, 2026)
The designation of Protected Rice Paddy Land (LSD) is a national policy aimed at controlling the conversion of agricultural land to ensure long-term food security. In practice, however, this policy often conflicts with factual conditions on the ground, particularly when residential housing projects have already been constructed and sold before the spatial utilization permits were fully obtained. This study aims to analyze the legal certainty of housing developments built on land that was later designated as LSD, and to identify appropriate legal protection mechanisms for good-faith purchasers. The Pendawa Housing Estate in Tegal Regency is used as a case study, and the research applies a normative juridical method based on statutory and case approaches. The findings reveal that LSD serves as an administrative instrument within the spatial planning system and should not be treated as an absolute prohibition on land use. Its implementation must be proportional and respect the principles of legal certainty and fairness, particularly concerning buyers who have acquired property lawfully. Legal responsibility for spatial violations lies with the developer, while local governments play a strategic role in resolving these issues through adaptive and equitable administrative law mechanisms. This study concludes that harmonization between LSD policies and regional spatial planning systems is essential, alongside the protection of good-faith stakeholders' rights in the context of residential development.